Model Pendidikan Minat dan Bakat Berbasis Multiple Intelligences: Tinjauan Literatur - Aisah Aisah; Dwi Anggi Apriani; Fifi Adita Nursida; Kamaluddin Kamaluddin; Dewi Safitri; Baiq Ida Astini (Badan Penerbit STIEPARI Press, 2024)
This research is a systematic literature review that aims to examine the application of the Multiple Intelligences (MI)-based interest and talent education model in the context of formal education. Literature sources were obtained from Google Scholar, Scispace, Directory of Open Access Journals (DOAJ), and Scopus databases with a publication range of 2015 to 2025. The results of the analysis show that the MI approach has great potential in creating an inclusive, personalised learning system that focuses on the holistic development of learners. MI is able to bridge the diversity of students' intelligence and interests so as to support the formation of a whole individual and the optimisation of their potential. However, the implementation of this model still faces significant obstacles, especially in the curriculum structure that is less flexible, the evaluation system that is still limited to cognitive aspects, low teacher readiness, and the lack of institutional support and collaborative culture. These findings indicate a gap between the theory and practice of implementing MI in formal education that needs attention for the development of more effective and inclusive education.